Competitiveness of Ukrainian oilseeds in the world market - Makhanova, Ju.M. (ХНУ ім. В. Н. Каразіна, 2012)
The article contains investigation of evaluating the competitiveness of the oil industry in Ukraine and determination of its competitive advantages to ensure their effective development. Characteristics of Ukraine’s oil branch in the global market are clarified.
В статье проведено исследование по оценке конкурентоспособности масличной отрасли Украины и определения ее конкурентных преимуществ, направленных на обеспечение их эффективного развития. Уточнены особенности деятельности масличной отрасли Украины на мировом рынке.
Keywords: competitive advantages; competitiveness; world market; oilseed